Psychometric Indicators of the Pro-environmental Attitudes' Questionnaire: Colombian Version - Willian Sierra Barón; Alba Lucia Meneses Baez (Frontiers in Psychology, 2022)
The detrimental effect of human behavior on the environment is undeniable. Attitudes are recognized as a predictor of the pro-environmental behavior; therefore, having good quality tools in Colombia to measure them is strategic to assess interventions. This study aims to establish psychometric indicators for the pro-environmental attitudes questionnaire (PEAQ) Colombian version to a sample of 415 volunteers (53% women and 47% men) aged 18–70 years (M = 40.28; SD = 14.06). We used the 28-item PEAQ already linguistically adapted for Colombia. We applied the following questionnaires: Environmental awareness (EA) (11 items), environmental values (EV) (4 items), and the pro-environmental at work questionnaire (PEWQ) (31 items). We used a one-parameter Rasch model and Winsteps program to assess the PEAQ's one-dimensionality and item statistics by gender, and estimated Spearman's rho coefficient between the PEAQ scores and the scales for concurrent validity. The PEAQ in this study has 24 items because 4 items did not fit into the Rasch model criteria. Its one-dimensionality was supported by an explained variance (43%) and the first residual variance (12%). The coefficients, α = 0.95 and Ω = 0.95; Rasch for persons = 0.90; and Rasch for items = 0.95. The correlation between the PEAQ and the EC, EV, and PEWQ scales were Spearman's rho coefficient = 0.859 (p ≤ 0.001), 0.795 (p ≤ 0.001), and 0.885 (p ≤ 0.001), respectively. Thus, the PEAQ Colombian version's psychometric indicators support it as a valid and reliable instrument to measure pro-environmental attitudes in this country.